2018
DOI: 10.1073/pnas.1721732115
|View full text |Cite
|
Sign up to set email alerts
|

Increase in chemokine CXCL1 by ERβ ligand treatment is a key mediator in promoting axon myelination

Abstract: SignificanceCXCL1 is a major neutrophil chemoattractant that binds to the chemokine receptor, CXCR2, on neutrophils and oligodendrocytes. Estrogen receptor β ligand treatment in a mouse model of multiple sclerosis induces an increase in peripheral and brain CXCL1 levels that correlate with an increase in axon remyelination. Oligodendrocyte progenitor recruitment and differentiation by CXCL1, in combination with attenuated IFN-γ production reducing apoptosis, may account for at least one avenue whereby estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…These peripheral actions of estradiol, promoting general body health, may also contribute to neuroprotection. For instance, the estrogenic regulation of peripheral immune responses (Morales et al, 2006;Karim et al, 2018) may impact on the protective actions of the hormone on autoimmune demyelinating diseases; the estrogenic regulation of adiposity and peripheral body metabolism (Rettberg et al, 2014) may improve brain bioenergetics; and the estrogenic signaling on peripheral organs may induce the release of tissue-specific cytokines with neuroprotective actions. Estradiol also affects gut microbiome composition (Kaliannan et al, 2018), which in turn may change the microbiota-gut-brain axis communication under brain neurodegenerative conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These peripheral actions of estradiol, promoting general body health, may also contribute to neuroprotection. For instance, the estrogenic regulation of peripheral immune responses (Morales et al, 2006;Karim et al, 2018) may impact on the protective actions of the hormone on autoimmune demyelinating diseases; the estrogenic regulation of adiposity and peripheral body metabolism (Rettberg et al, 2014) may improve brain bioenergetics; and the estrogenic signaling on peripheral organs may induce the release of tissue-specific cytokines with neuroprotective actions. Estradiol also affects gut microbiome composition (Kaliannan et al, 2018), which in turn may change the microbiota-gut-brain axis communication under brain neurodegenerative conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The ERβ selective agonist DPN is neuroprotective in the hippocampus of chronic hypertensive rats (Pietranera et al, 2016) and increases GFAP expression in astrocytes and decreases neuronal apoptosis in co-cultures of astrocytes and neurons exposed to oxygen glucose deprivation and reperfusion (Ma et al, 2016). Protective actions of DPN and other ERβ ligands, such has indazole-Cl and WAY-202041, have been also characterized in mouse models of multiple sclerosis, where they stimulate endogenous myelination and functional recovery (Atkinson et al, 2019;Khalaj et al, 2016;Karim et al, 2018Karim et al, , 2019) (see also Section 4.8). Furthermore, ERβ expressed in astrocytes mediates the protective effect of estradiol on neurons exposed to oxygen-glucose deprivation and reperfusion (Ma et al, 2016) and ERβ regulates inflammasome activation and protects from global cerebral ischemia in senescent female rats (de Rivero-Vaccari et al, 2016).…”
Section: Cerebral Cortexmentioning
confidence: 99%
“…Interestingly, it has been shown that treatment of EAE-induced mice with ERβ ligands drastically reduced EAE severity. This correlated with increased astroglial production of CXCL1, leading to improved remyelination and neuroprotection [79].…”
Section: Pathophysiological Roles Of Activated Astrocytes In Ms and Ementioning
confidence: 99%
“…Coronal brain sections (bregma +0.85 to +0.95 mm, plates 23–24) with CC but no hippocampus (rostral slices) or sections (bregma −1.90 to −2.0 mm, plates 47–48) containing medial hippocampus (caudal slices) were used (Paxinos and Franklin, 2012; Karim et al, 2018). The brain slices were permeabilized, blocked in normal goat serum, and immunolabeled with primary antibodies shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…We address remyelination events using behavior, immunohistochemistry (IHC), electron microscopy and electrophysiology to further understand axon pathology and functional remyelination. Recognizing the potential for rapamycin to optimize the cuprizone model by producing more complete demyelination, we sought to characterize the effects of rapamycin treatment during cuprizone diet on axonal conduction and myelination in the largest white matter tract in the brain, the corpus callosum (CC), that is coherently affected by CPZ diet (Patel et al, 2013; Moore et al, 2014; Hasselmann et al, 2017; Lapato et al, 2017; Karim et al, 2018). In this study, mice were divided between three groups: normal diet (ND), demyelination (CPZ), and remyelination (CPZ + ND).…”
Section: Introductionmentioning
confidence: 99%